Directed Flow of Λ, Λ3H and Λ4H in Au+Au collisions at √sNN = 3.2, 3.5, 3.9 and 4.5 GeV at RHIC - Han Junyi (EPJ Web of Conferences)
Studying hyper-nuclei yields and their collectivity can shed light on their production mechanism as well as the hyperon-nucleon interactions. Heavy-ion collisions from the RHIC beam energy scan phase II (BES-II) provide an unique opportunity to understand these at high baryon densities. In these proceedings, we present a systematic study on energy dependence of the directed flow (v1) for Λ and hyper-nuclei (3ΛH and 4ΛH) from mid-central Au+Au collisions at √sNN = 3.2, 3.5, 3.9 and 4.5 GeV, collected by the STAR experiment with the fixed-target mode during BES-II. The rapidity (y) dependence of the hyper-nuclei v1 is studied in mid-central collisions. The extracted v1 slopes (dv1/dy|y=0) of the hyper-nuclei are positive and decrease gradually as the collision energy increases. These hyper-nuclei results are compared to that of light-nuclei including p, d, t/3He and 4He. Finally, these results are compared with a hadronic transport model including coalescence after-burner.